2019
DOI: 10.29252/jhehp.5.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Accident Modeling in Small-scale Construction Projects Based on Artificial Neural Networks

Abstract: Journal of Human, Environment, and Health PromotionJournal homepage: www.zums.ac.ir/jhehp Background: Several factors contribute to accidents in small-scale construction projects (SSCPs). The present study aimed to assess the influential factors in SSCP accidents and introduce a model to predict their frequency. Methods: In total, 38 SSCPs were within the scope of this investigation. The safety index of accident frequency rate (AFR) causing 452 injury construction accidents during 12 years (2007)(2008)(2009)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In Saudi Arabia, a large proportion of the local construction contractors are SMSCs. As evidenced in developed countries, the safety performance of SMSCs is lower than that of larger construction companies [15]. When faced with issues like scarcity of project resources, the SMSCs are not likely to provide adequate funds for managing construction safety [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, a large proportion of the local construction contractors are SMSCs. As evidenced in developed countries, the safety performance of SMSCs is lower than that of larger construction companies [15]. When faced with issues like scarcity of project resources, the SMSCs are not likely to provide adequate funds for managing construction safety [14].…”
Section: Methodsmentioning
confidence: 99%
“…When faced with issues like scarcity of project resources, the SMSCs are not likely to provide adequate funds for managing construction safety [14]. Alizadeh [15] observed that SMSCs usually have a safety plan and safety professional on board, not because the companies have a real safety commitment. Still, for the reason that top management feels that it is an essential evil.…”
Section: Methodsmentioning
confidence: 99%